PENGARUH E-WOM, KEPERCAYAAN KONSUMEN DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE MS GLOW DI KOTA BATAM - Gulo, Icalni; Suhardi, Suhardi (LPPM Universitas Putera Batam, 2025)
This research aims to analyze the impact of e-wom, consumer trust and brand awareness on purchasing decisions for MS Glow Skincare products in Batam City. This study applies a quantitative research approach. This study involved 100 respondents consisting of people who have purchased and used MS Glow Skincare products in Sagulung District, Batam City. The data collection method applied was through a questionnaire. Data processing was carried out using SPSS software version 26. According to the data and analysis that have been carried out, this study shows that e-wom has a positive and significant influence on purchasing decisions for MS Glow Skincare products in Batam City. In addition, consumer trust has a positive and significant influence on purchasing decisions for MS Glow Skincare products in Batam City. The brand awareness variable has a positive and significant influence on purchasing decisions for MS Glow Skincare products in Batam City. Simultaneously, e-wom, consumer trust and brand awareness have a positive and significant influence on purchasing decisions for MS Glow Skincare products in Batam City.